Notch and Numb are required for normal migration of peripheral glia in Drosophila. - Edenfeld, G.; Altenhein, B.; Zierau, A.; Cleppien, D.; Krukkert, K.; Technau, G.; Klambt, C. (Developmental Biology, 2007)
A prominent feature of glial cells is their ability to migrate along axons to finally wrap and insulate them. In the embryonic Drosophila PNS, most glial cells are born in the CNS and have to migrate to reach their final destinations. To understand how migration of the peripheral glia is regulated, we have conducted a genetic screen looking for mutants that disrupt the normal glial pattern. Here we present an analysis of two of these mutants: Notch and numb. Complete loss of Notch function leads to an increase in the number of glial cells. Embryos hemizygous for the weak Notch(B-8X) allele display an irregular migration phenotype and mutant glial cells show an increased formation of filopodia-like structures. A similar phenotype occurs in embryos carrying the Notch(ts1) allele when shifted to the restrictive temperature during the glial cell migration phase, suggesting that Notch must be activated during glial migration. This is corroborated by the fact that cell-specific reduction of Notch activity in glial cells by directed numb expression also results in similar migration phenotypes. Since the glial migration phenotypes of Notch and numb mutants resemble each other, our data support a model where the precise temporal and quantitative regulation of Numb and Notch activity is not only required during fate decisions but also later during glial differentiation and migration.